A high proportion of cells carrying trisomy 12 is associated with a worse outcome in patients with chronic lymphocytic leukemia. Issue 2 (17th February 2015) - González‐Gascón y Marín, Isabel; Hernández‐Sánchez, María; Rodríguez‐Vicente, Ana‐Eugenia; Sanzo, Carmen; Aventín, Anna; Puiggros, Anna; Collado, Rosa; Heras, Cecilia; Muñoz, Carolina; Delgado, Julio; Ortega, Margarita; González, María‐Teresa; et al.
Abstract: The prognosis of chronic lymphocytic leukemia (CLL) patients displaying trisomy 12 (+12) remains unclear. In this study, we analyzed the influence of the proportion of cells with +12, and other clinical and biologic factors, in time to first therapy (TTFT) and overall survival (OS), in 289 patients diagnosed with CLL carrying +12. Median OS was 129 months. One hundred seventy‐four patients (60.2%) presented +12 in <60% of cells. TTFT and OS for this subgroup were longer than for the subgroup with +12 in ≥60% of cells, with a median TTFT of 49 months (CI95%, 39–58) vs 30 months (CI95%, 22–38) ( P  = 0.001); and a median OS of 159 months (CI95%, 119–182), vs 96 months (CI95%, 58–134) ( P  = 0.015). Other factors associated with a shorter TTFT were: Binet stage, B symptoms, lymphadenopathy, splenomegaly, high lymphocyte count, 11q‐, high β2 microglobulin, and high LDH. In the multivariate analysis, clinical stage, +12 in ≥60% of cells, high lymphocyte count, B symptoms, and 11q‐ in addition, resulted of significance in predicting shorter TTFT. Significant variables for OS were: Binet stage, lymphadenopathy, splenomegaly, high LDH, high β2 microglobulin, 11q‐, and CD38. In the multivariate analysis, only Binet stage, 11q‐, and high β2microglobulin significantly predicted shorter OS. CLL with +12 entails a heterogeneous group with intermediate prognosis. However, a high proportion of cells carrying +12 separates a subgroup of patients with poor outcome. Copyright © 2015 John Wiley & Sons, Ltd.